2010
DOI: 10.1038/cmi.2009.107
|View full text |Cite|
|
Sign up to set email alerts
|

TGF-β1 gene-modified, immature dendritic cells delay the development of inflammatory bowel disease by inducing CD4+Foxp3+ regulatory T cells

Abstract: Inflammatory bowel disease (IBD) is caused by an uncontrolled immune response in the intestinal lumen, leading to inflammation in genetically predisposed individuals. Immunotherapy may be a promising approach to the treatment of IBD. Here, we show that transforming growth factor-b1 (TGF-b1) gene-modified immature dendritic cells (imDCs) could enhance the inhibitory function of imDCs and delay the progress of IBD induced by dextran sodium sulfate in mice. The results of fluorescence-activated cell sorter (FACS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 23 publications
2
15
0
1
Order By: Relevance
“…In this study, imDCs produced IL‐10 themselves in vitro , and IL‐10 gene transduction boosted the production of IL‐10 more than four times. IL‐10 gene‐transduced imDCs had stable low expression of CD80, CD86 and MHC II, and, upon co‐culture with T cells, promoted the secretion of TGF‐β1, which is a Th2 type cytokine that inhibits the activation and proliferation of cytotoxic T lymphocytes . Mixed lymphocyte reactions detected lower levels of TNF‐a in the supernatant of allogenic lymphocytes cocultured with IL‐10/imDCs than that in imDC, which is similar to previous results reporting that IL‐10 inhibited the secretion of Th1 cell cytokines.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, imDCs produced IL‐10 themselves in vitro , and IL‐10 gene transduction boosted the production of IL‐10 more than four times. IL‐10 gene‐transduced imDCs had stable low expression of CD80, CD86 and MHC II, and, upon co‐culture with T cells, promoted the secretion of TGF‐β1, which is a Th2 type cytokine that inhibits the activation and proliferation of cytotoxic T lymphocytes . Mixed lymphocyte reactions detected lower levels of TNF‐a in the supernatant of allogenic lymphocytes cocultured with IL‐10/imDCs than that in imDC, which is similar to previous results reporting that IL‐10 inhibited the secretion of Th1 cell cytokines.…”
Section: Discussionsupporting
confidence: 87%
“…93 In addition, the therapeutic potential of DCs in IBD has also been recognized, with TGF-b1 gene-modified and regulatory probiotic-induced DCs suppressing murine models of intestinal inflammation. 94,95 Work on thymic stromal lymphopoietin (TSLP), a hematopoietic cytokine secreted by the IEC, has shown that dysregulated IEC-intrinsic TSLP expression directly affects the production of DC-derived proinflammatory cytokines. 96 It has also been shown that TSLP and as-yet unidentified IEC-derived factors induce TSLP receptor expression on mucosal DCs, which may skew the normal Th1/Th2 balance, with altered expression in CD patients also described.…”
Section: Antigen Recognitionmentioning
confidence: 99%
“…TGF-β1 is a negative regulator of pro-inflammatory immune responses. We previously found that systemic administration of TGF-β1 gene-modified immature DCs delayed the development of dextran sulfate sodiuminduced murine inflammatory bowel disease (IBD) [4]. Therefore, * These authors contributed equally to this work.…”
mentioning
confidence: 99%